Rotational Studies on Isomers of benzene containing Bicyclopropenyl Rings - Jeevan, Jebakumar; Gopalan, R. (Asian Journal of Chemistry, 2010)
Molecular orbital calculations have been carried out at the AM1 level with isomers of benzene having two cyclopropenyl rings. Rotational study of the single bond connecting the two cyclopropenyl moieties resulted in the variation of the total energy of the molecule. Based on these variations, two isomers were found to have interaction between the two classical π-bonds, namely, 1,1'-bicyclopropenyl and 3,3'-bicyclopropenyl. These molecules have relatively larger rotational barrier compared to 1,3'-bicyclopropenyl. An analysis of the wave functions and the charge densities of these show an accumulation of electronic charge in the pz orbital of the methylene (or methine) carbon C3 in the cyclopropenyl.